2022
DOI: 10.3390/ijerph19052499
|View full text |Cite
|
Sign up to set email alerts
|

Congestive Nephropathy

Abstract: The complex interaction between cardiac and renal functions is known. However, when these functions are disrupted, many intricate and sensitive interactions between these organs are failed by several pathophysiological ways. As a result, this malfunction is clinically evident by sign and symptoms associated to intravascular and interstitial congestion. In this sense, the adverse impact of venous congestion on renal function has long been recognized. Currently, the presence of a specific subtype of nephropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As the kidney receives 20% of the cardiac output, it is vulnerable to global hypoperfusion, and circulatory shock is one potential factor responsible for renal injury (2, 32). Furthermore, general anesthesia, fluid therapy, surgical trauma, blood loss, and repositioning of the stomach leads to congestive nephropathy, IRI, damage induced by pro-inflammatory cytokines, and oxidative stress in dogs with GDV (1,3,33). Renal ischemic injury causes damage to the glomerulus, renal tubular cells, and renal vasculature (32).…”
Section: Discussionmentioning
confidence: 99%
“…As the kidney receives 20% of the cardiac output, it is vulnerable to global hypoperfusion, and circulatory shock is one potential factor responsible for renal injury (2, 32). Furthermore, general anesthesia, fluid therapy, surgical trauma, blood loss, and repositioning of the stomach leads to congestive nephropathy, IRI, damage induced by pro-inflammatory cytokines, and oxidative stress in dogs with GDV (1,3,33). Renal ischemic injury causes damage to the glomerulus, renal tubular cells, and renal vasculature (32).…”
Section: Discussionmentioning
confidence: 99%
“…In individuals experiencing systemic congestion, the elevation in central venous pressure induces renal venous congestion, precipitating an augmentation in renal interstitial hydrostatic pressure due to the limited expansibility of the encapsulated kidney. Consequently, there ensues a simultaneous rise in the glomerular transcapillary hydrostatic pressure gradient, initiating glomerular hyperfiltration initially but potentially compromising both glomerular filtration rate (GFR) and renal blood flow subsequently Figure 1 [ 18 , 19 ]. The kidneys endeavor to sustain pressures by augmenting lymphatic outflow, yet a persistent increase in central venous pressure ultimately diminishes lymphatic outflow[ 20 ].…”
Section: Congestive Nephropathymentioning
confidence: 99%
“…In addition, end-organ effects of fluid overload are being increasingly recognized, which brings us to the topic of congestive nephropathy. Congestive nephropathy is defined as renal dysfunction that occurs due to venous congestion leading to impaired organ perfusion[ 7 ]. While this term was recently coined[ 8 ], several studies have previously shown that elevated central venous pressure (CVP) is associated with worsening renal function despite preserved cardiac index[ 9 ].…”
Section: Introductionmentioning
confidence: 99%